2018 10th International Conference on Intelligent Human-Machine Systems and Cybernetics (IHMSC) 2018
DOI: 10.1109/ihmsc.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Rise of Digital Media to Triumph Brand Loyalty

Abstract: Modern era of management has seen a rise in the level of customer engagement, which was not that much of importance earlier. Earlier, brands tend to compete on the products or service they offer. In the recent digital era, it is much more than what a brand has to offer. The emergence of digital media has boosted the importance of customer engagement. Now, customers can easily get in touch with the companies through digital channels. Corporations use these channels to let customers aware about their offerings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the current competitive and dynamic environment, firms, besides other factors, need to develop a sustainable relationship with consumers. Besides other factors, this sustainable relationship depends on trust between customers and firms (Donney & Cannon, 1997;Kazmi et al, 2016a).Extant literature has documented that consumers' experience of goods and services affects their trust and loyalty. If they had a pleasant experience with the goods and services, they would have a positive attitude towards purchase intention, leading to higher CL and satisfaction (Xie et al, 2015;.…”
Section: Hypothesis Development Consequences Of Illusive Promotionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current competitive and dynamic environment, firms, besides other factors, need to develop a sustainable relationship with consumers. Besides other factors, this sustainable relationship depends on trust between customers and firms (Donney & Cannon, 1997;Kazmi et al, 2016a).Extant literature has documented that consumers' experience of goods and services affects their trust and loyalty. If they had a pleasant experience with the goods and services, they would have a positive attitude towards purchase intention, leading to higher CL and satisfaction (Xie et al, 2015;.…”
Section: Hypothesis Development Consequences Of Illusive Promotionmentioning
confidence: 99%
“…Furthermore, it also indirectly affects customer loyalty. (Richard & Zhang 2012; Kazmi et al, 2018;Mazhar et al, 2022). Another study found that consumers have a higher loyalty for firms with higher corporate image and reputation (Nguyen & Leblanc, 2001).…”
Section: Corporate Imagementioning
confidence: 99%
“…The results are consistent with Aziz (2019), Ahmed and Khan (2019) and contrary to Maroof et al (Maroof et al, 2019), Shafique et al (2019) and Biblop (Biplob, 2017). Further, if we are able to find empirical evidences against the efficient market hypothesis, the same data set upon increasing the sample size, time frame and country, may reflect contrasting outcomes (Kazmi, Abid, Iqbal, & Hai, 2016; Kazmi, Wahab, Zaman, & Kou, 2018). Strategies based on the results will not always lead to consistent returns in future.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%